The Effect of Taxpayer Awareness, Modernization of the Tax System, and Tax Amnesty on Taxpayer Compliance for Micro, Small and Medium Enterprises (MSMEs) - Septina, Della; Dyarini, Dyarini (Dinasti Publisher, 2025)
In this study, the degree of tax compliance among Indonesian micro, small, and medium-sized businesses will be assessed in relation to taxpayer awareness, tax system modernization, and tax amnesty. The South Tangerang District's MSME taxpayers served as the study's subjects. A straightforward random selection technique combined with probability sampling was used to choose 100 responders in total. A quantitative methodology backed by descriptive statistical analysis was used in the investigation. SPSS version 25 was used to process the data, and the findings indicate that modernization of the tax system, tax amnesty, and taxpayer comprehension have a positive and significant influence on taxpayer compliance. It can be said that improving taxpayer comprehension, making it easier to obtain information through a modernized tax system, and enacting tax amnesty laws may all help increase MSME taxpayers' tax compliance.